An integrated approach to river valley revitalisation - Nawieśniak-Caesar, Maria; Wilkosz-Mamcarczyk, Magdalena; Hernik, Józef; Gorzelany, Julia; Gorzelany-Dziadkowiec, Magdalena (Journal of Environmental Engineering and Landscape Management, 2019)
Rivers have always been a unique space in urban landscapes. Regrettably, the river-town relationship was disturbed in the 19th and at the beginning of the 20th century as industrial plants and districts were established at banks, which changed the urban structure. This resulted in degradation of riverscapes among other things. Today, attempts are made to revitalise the areas and use them for ecological, recreational, and other purposes. The paper presents an integrated approach to river valley revitalisation – demonstrated on the Skawinka river, flowing through Skawina, an industrial town in Poland. An integrated approach could indicate local development possibilities of river valley and thereby strengthen the competitiveness of the area. The study employed the Landscape and Hydromorphological Assessment of River Valleys Method, focusing on hydromorphological, landscape, and integrated factors. Proposing an integrated approach to the Skawinka river valley revitalisation presents a procedure that indicates possibilities for local development and thereby strengthening the competitiveness of this region. The guidelines for the revitalisation project for this river indicate that if the river was made generally accessible, it may become an important location for social and economic life. At the same time it might have a recreational and educational function.